1996
DOI: 10.1051/agro:19961016
|View full text |Cite
|
Sign up to set email alerts
|

Soluble proteins and polypeptide profiles of spores of arbuscular mycorrhizal fungi. Interspecific variability and effects of host (myc+) and non-host (myc-) Pisum sativum root exudates

Abstract: d'un génotype non-hôte (P2) de P sativum a aussi été effectuée. Bien que de faibles stimulations dans la croissance des hyphes aient été obtenues dans les exudats racinaires par rapport à l'eau, aucune différence dans le profil polypeptidique n'a été observée.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…when we compared the set of the additional polypeptides identified by the present work in the myc"^ genotypes to the profile of germinating spores of G. mosseae (Samra et al, 19966), only two polypeptides (MW 32, 45 and pi 6-6, 6-2) were observed in both AM roots and fungal material. Therefore, these two polypeptides could represent material from fungal cells colonizing the roots, whereas the others could be symbiosis-related polypeptides.…”
Section: Up and Down Regulation Of Preexisting Polypeptidesmentioning
confidence: 92%
“…when we compared the set of the additional polypeptides identified by the present work in the myc"^ genotypes to the profile of germinating spores of G. mosseae (Samra et al, 19966), only two polypeptides (MW 32, 45 and pi 6-6, 6-2) were observed in both AM roots and fungal material. Therefore, these two polypeptides could represent material from fungal cells colonizing the roots, whereas the others could be symbiosis-related polypeptides.…”
Section: Up and Down Regulation Of Preexisting Polypeptidesmentioning
confidence: 92%
“…n-Aguilar & Barea, 1996 ;Gianinazzi-Pearson, 1996). Although much is known about colonization at the structural level, we still know very little about the genes and gene-products involved in this process.…”
Section: mentioning
confidence: 99%
“…As a consequence of AM colonization, roots undergo anatomical, histological, metabolic and genetic modifications (for review see Bonfante & Perotto, 1995 ;Azco! n-Aguilar & Barea, 1996 ;Gianinazzi-Pearson, 1996). Although much is known about colonization at the structural level, we still know very little about the genes and gene-products involved in this process.…”
Section: mentioning
confidence: 99%
“…The first fungal protein extracts analysed by polyacrylamide gel electrophoresis were obtained from spores (Sanders et al 1992). Changes in polypeptide patterns in germinating spores induced by the presence of root exudates were later detected by 2D gel electrophoresis (Samra et al 1996) and the identification of fungal proteins by mass spectrometry analysis was achieved for extraradical hyphae from root organ cultures (Dumas-Gaudot et al 2004). Later, fungal proteins could be also detected inside roots (Recorbet et al 2010).…”
Section: Methodologiesmentioning
confidence: 99%
“…The extensive branching of the germinating hyphae goes along with dramatic changes in polypeptide patterns (Samra et al 1996). Interestingly the first molecular analysis down to a particular gene was conducted during the stimulation of presymbiotic development by a so-called mycorrhiza helper bacterium, a particular Bacillus subtilis strain (Requena et al 1999).…”
Section: Arbuscular Mycorrhizal Fungal Development a From Dormanmentioning
confidence: 99%